Neutron induced alpha production from carbon between 18 and 22 MeV - Stevens, Alun Peter (Department of Physics, 2016)
Cross sections for neutron induced alpha production in carbon were measured at seventeen energies between 18 and 22 MeV, using a deuterated anthracene crystal as both target and detector. Pulse shape discrimination was employed to separate the alphas and elastically scattered deuterons from the other reaction products. Published (n,d) elastic scattering data were used as a standard to obtain the alpha production cross sections. Comparison with available measurements shows good agreement